RUSSIA, CHINA, EUROPE, EURASIA AND THE USA: COVID-2019 AND AFTER – WHAT OUR FUTURE MAY BE? SUMMARY OF THE ONLINE INTERNATIONAL ROUNDTABLE DISCUSSION - A. D. Voskressenski (Сравнительная политика)
Summary of the online international roundtable discussion “Russia, China, Europe, Eurasia and the USA: COVID-2019 and after – What Our Future May Be?” taken place on April, 11, 2020 via Zoom as an online conference*. The topics discussed are: perception of China in different countries, Russian-Chinese partnership, and its Role, US / China / Russia’s changing international role after COVID-19, SARSCov-2019/COVOD-2019; COVID-19 and its consequences for international order; China, Europe and the USA political economy models and COVID-19.The conference was organized in the frameworks of the online academic events series of the Centre for Comprehensive Chinese Studies and Regional Projects, MGIMO University: “The World-Eurasia-China Agenda and Regional Problematique. OnLine Discussions”.